Cephalometric analysis of Malay children with and without unilateral cleft lip and palate - Ebin Lillybia Emily; Zam Norzakiah Mohamed Zam; Othman Siti Adibah (Australasian Orthodontic Journal, 2023)
To investigate the craniofacial morphology of Malay children with repaired UCLP and compare the data with non-cleft Malay children.